Effectiveness of the Workshop Program on Teenage Pregnancy Prevention for Public Health Volunteers - Boonwiwat, Pilairat (Journal of Health Science of Thailand, 2017)
The purpose of this action research was to study the effectiveness of the workshop program on teenage pregnancy prevention for public health volunteers (PHV) in Samut Sakhon Province. Assessment of the program involved (1) examining levels of knowledge, attitude, and practices of PHVs on the teenage pregnancy prevention prior to the workshop, right after the workshop, and also 6 months after the workshop, (2) measuring levels of satisfaction of PHVs on the workshop and (3) measuring levels of propriety of subject contents. Samples study included 58 PHVs, lower than 60 years of age, with elementary education, and voluntarily participated in this research project. Quantitative data were collected through questionnaire on attitude, practices, satisfaction on the workshop and propriety of the subject contents. Statistics including frequency distribution, percentage, means, standard deviation, dependent t-test, and multiple regression Analysis were applied. The result showed that right after and 6 month after the workshop, PHVs’ levels of knowledge and practices on the teenage pregnancy prevention were high while PHVs’ attitude was at the medium level. It was also found that levels of knowledge, practices and attitude after the workshop were significantly higher than those prior to the workshop (p<0.01), and predicted equations for PHVs’ knowledge and attitude statistically correlated with the PHVs’ practice, Adj R2 = 84.70 percent. Most PHVs were highly satisfied the workshop, at the percentage of 65.52 - 86.21; and expressed that all topics of the workshop were highly appropriate, at percentage 79.31 - 93.10. The workshop program on teenage pregnancy prevention could increase the PHV’s knowledge, attitude, and proper practices. Therefore, the author recommended to use the workshop program for the development of PHVs in all other areas of the Province.